1994
DOI: 10.1159/000129326
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the Release of Tissue Kallikrein in Experimental Pancreatitis in the Pig

Abstract: The activation of the kallikrein-kinin system is thought to be one of the pathophysiological factors in acute pancreatitis. A radioimmunoassay for porcine, pancreatic tissue kallikrein was developed and used to measure levels in normal plasma and peritoneal fluid and in experimental, bile-induced (group and bile trypsin-induced (group B) acute pancreatitis in the pig. Normal porcine plasma and peritoneal fluid contained about 2.17 ± 0.11 and 1.91 ± 0.19 µg/l (SEM) tissue kallikrein, respectively. In experiment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1995
1995
2001
2001

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Blood sampling from the liver veins would have revealed that, but such sampling was regarded as too hazardous and inconvenient for the volunteer. Intravenous injection of radiolabelled tissue kallikrein may mimic the release of tissue kallikrein seen in in¯ammatory disorders such as acute pancreatitis [7,8]. Already 2 min after injection the major part of the 125 I-tissue kallikrein seemed to be bound to an inhibitor with a molecular weight of about 50 ± 70 kDa, as indicated by gel ® ltration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Blood sampling from the liver veins would have revealed that, but such sampling was regarded as too hazardous and inconvenient for the volunteer. Intravenous injection of radiolabelled tissue kallikrein may mimic the release of tissue kallikrein seen in in¯ammatory disorders such as acute pancreatitis [7,8]. Already 2 min after injection the major part of the 125 I-tissue kallikrein seemed to be bound to an inhibitor with a molecular weight of about 50 ± 70 kDa, as indicated by gel ® ltration.…”
Section: Discussionmentioning
confidence: 99%
“…It is a serineprotease [3] which releases pharmacologically highly active bradykinin from kininogen by limited proteolysis [3,4]. Tissue kallikrein is believed to be involved in both physiological processes such as blood pressure control [1] and in haemostasis [5], as well as pathophysiological processes as hypertension, diabetes, ulcerative colitis, Cushing' s disease, Alzheimer's disease, arthritis [1], asthma [6] and pancreatitis [7,8]. In vitro studies have shown different interactions between tissue kallikrein and the plasma proteinase inhibitors in human blood [9] compared with other mammals such as the pig [10].…”
mentioning
confidence: 99%